2017
DOI: 10.3390/su9081330
|View full text |Cite
|
Sign up to set email alerts
|

A New Dynamic Pricing Model for the Effective Sustainability of Perishable Product Life Cycle

Abstract: Perishable products run their life cycle in a short period of time due to the shortness of their shelf lives. Product efficiency falls when especially non-recyclable products are thrown away without being used. Furthermore, this kind of products that unnecessarily occupy shelves of supermarkets cause supermarkets to follow an insufficient stock management policy. Unconscious and unplanned use of our limited natural resources will deteriorate the product portfolio for future generations. Such unconscious produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Numerous earlier studies have focused on showing the benefits of implementing dynamic pricing for perishables [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Past studies using a deterministic simulation showed that inventory aging of perishable foods can be reduced by applying various dynamic pricing strategies [25]. Past studies using consumer need-driven demand scenarios showed that more dynamic pricing and earlier discount can enhance the sales volume, reduce wastage, and inventory aging when consumers' requirement regarding remaining days left follow normal distribution and retailers can accurate measure average demand or the target stock amount exceeds average demand [5,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous earlier studies have focused on showing the benefits of implementing dynamic pricing for perishables [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Past studies using a deterministic simulation showed that inventory aging of perishable foods can be reduced by applying various dynamic pricing strategies [25]. Past studies using consumer need-driven demand scenarios showed that more dynamic pricing and earlier discount can enhance the sales volume, reduce wastage, and inventory aging when consumers' requirement regarding remaining days left follow normal distribution and retailers can accurate measure average demand or the target stock amount exceeds average demand [5,27].…”
Section: Discussionmentioning
confidence: 99%
“…They investigated the optimal timing and discount rate and replenishment policy for aged perishable products. Tekin and Erol [25] developed a new dynamic pricing for perishable foods with a short selling period. They analyzed interactions among price, profitability, and cost in detail using a deterministic simulation model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 20 years, there have been many achievements in dynamic pricing considering multiple products, competition, and limited demand information, under the three basic assumptions of finite time horizon, finite amount of inventory, and dynamic pricing [9]. With regard to the perishable product life cycle, Tekin and Erol proposed a dynamic pricing model to maximize the profits of supermarkets and product utilization rates [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, let u ∈ [0, 1] be the control decision of group booking; when the group order is rejected u = 0, otherwise u = 1. The booking limit for group orders is dependent on Equation (10).…”
Section: Optimal Policymentioning
confidence: 99%